2017
DOI: 10.1073/pnas.1618858114
|View full text |Cite
|
Sign up to set email alerts
|

Global analysis of depletion and recovery of seabed biota after bottom trawling disturbance

Abstract: Bottom trawling is the most widespread human activity affecting seabed habitats. Here, we collate all available data for experimental and comparative studies of trawling impacts on whole communities of seabed macroinvertebrates on sedimentary habitats and develop widely applicable methods to estimate depletion and recovery rates of biota after trawling. Depletion of biota and trawl penetration into the seabed are highly correlated. Otter trawls caused the least depletion, removing 6% of biota per pass and pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
292
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 278 publications
(299 citation statements)
references
References 35 publications
3
292
1
3
Order By: Relevance
“…Brief examples and performance‐based analyses are used to develop guidance on best practices for a wide range of fisheries and associated management systems. Building on previous analyses of the impacts and management of trawling activities (Collie et al, ; Hiddink et al, , ; Pitcher et al, ; Sciberras et al, ), we address multiple knowledge gaps identified in a prioritization exercise concerned with reducing the environmental impacts of trawling (Kaiser et al, ). The resulting guidance on best practices is intended to help managers and the industry minimize environmental impacts of trawling per unit weight or value of landed fish, while achieving a sustainable level of fish production.…”
Section: Introductionmentioning
confidence: 99%
“…Brief examples and performance‐based analyses are used to develop guidance on best practices for a wide range of fisheries and associated management systems. Building on previous analyses of the impacts and management of trawling activities (Collie et al, ; Hiddink et al, , ; Pitcher et al, ; Sciberras et al, ), we address multiple knowledge gaps identified in a prioritization exercise concerned with reducing the environmental impacts of trawling (Kaiser et al, ). The resulting guidance on best practices is intended to help managers and the industry minimize environmental impacts of trawling per unit weight or value of landed fish, while achieving a sustainable level of fish production.…”
Section: Introductionmentioning
confidence: 99%
“…Although they are economically valuable, scallop dredge fisheries have well‐known adverse effects on benthic communities, leading to reductions in diversity and production (Kaiser, Collie, Hall, Jennings, & Poiner, ; Lambert, Jennings, Kaiser, Davies, & Hiddink, ). Nevertheless, the effects of scallop dredging vary considerably according to the environmental context in which scallop dredging occurs, such that some benthic communities exhibit higher resilience to disturbance than others (Hiddink et al., , ). Of particular concern are the effects of dredges (and other towed mobile fishing gears) on stable biogenic habitats, such as reefs, or on longer‐lived fauna.…”
Section: Introductionmentioning
confidence: 99%
“…Two advances in technology are creating new opportunities for global‐scale synthesis of hard‐to‐observe habitats. First, models based on meta‐analysis of experimental trawling may allow global estimation of the impacts of trawling on soft‐sediment habitats (Hiddink et al., ). Second, video monitoring and automated image analysis are enhancing capacity to observe large areas of habitats, particularly in areas that are difficult to survey with conventional methods (e.g., Ferrari et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have documented impacts of trawl disturbance on soft‐sediment fish habitats, but these effects include both direct long‐term negative impacts of trawling on habitats that improve juvenile survival and positive food subsidies to fish because injured or dying fauna are left in the wake of trawling gear (Collie et al., ). Soft‐sediment regions provide a wide variety of important habitats to numerous fisheries species, but these different habitats vary widely in their resilience to trawl disturbance (Hiddink et al., ). Future modelling studies could combine estimates of biogenic habitat resilience with maps of habitat types to estimate the global impact of trawling on biogenic seabed habitats (Hiddink et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation